Green Roofs for Grey Water Treatment – Comparative Study of Economic and Environmental Impacts - Attia, Shaden S (AUC Knowledge Fountain, 2026)
Cities are under more pressure than ever to use sustainable methods for managing water and other resources because of urbanization, climate change, and a lack of water. Standard greywater treatment systems (SGTSs) work well, but they use a lot of resources and don't provide a lot of ecosystem services. Greywater-treating green roofs (GTGRs) have emerged as a promising Nature-Based Solution (NBS), combining wastewater recycling with benefits like regulating temperature, reducing greenhouse gas (GHG) emissions, and reducing the urban heat island (UHI) effect. Even with this potential, there is still not enough real-world research on how GTGRs affect both the economy and the environment, especially in different regions. This thesis fills this gap by comparing GTGRs to SGTSs, focusing on both environmental and economic results. This study aims to evaluate ‘intensive modified’ and ‘integrated systems’ GTGR intakes through cost and performance modelling. This is done through Life Cycle Costing (LCC) and Thermal modelling which are visualized through Power BI linked to Excel and multifaceted simulations. The McDA is case studied with variances in the Spanish and Egyptian climates and economics to use as a balance in the cross-regional foundation model. The results showed that GTGR systems save water meant for human consumption and decrease CO2 emissions, leading to substantial positive environmental impact. Economic performance remains extremely context reliant. All three systems in Spain are cost-efficient, while negative and positive Net Present Values (NPV) with reasonable payback periods are still usable for SGTS systems. This is not the case for Egypt, where only the SFIGR system is deemed economically feasible, while hydroponic and advanced systems are still financially non-viable. These results indicate that there are specific gaps in policy for the design of GTGR technologies that need to be filled in order to ensure that it is usable at scale. 4 The study acknowledges certain limitations, including reliance on secondary cost data, the application of generalized emission factors, and the exclusion of indirect co-benefits such as biodiversity enhancement and social well-being. Nevertheless, the results provide critical insights into the trade- offs and synergies of GTGRs and offer evidence-based recommendations for policy and practice. Ultimately, this research concludes that GTGRs can play a strategic role in sustainable urban water management and climate adaptation, directly contributing to the achievement of SDG 6 (Clean Water and Sanitation), SDG 11 (Sustainable Cities and Communities), and SDG 13 (Climate Action).